Dressed (renormalized) coordinates in a nonlinear system - Flores-Hidalgo, G.; Milla, Y. W. (Iop Publishing Ltd, 2005)
In previous publications, the concepts of dressed coordinates and dressed states have been introduced in the context of a harmonic oscillator linearly coupled to an infinity set of other harmonic oscillators. In this paper, we show how to generalize such dressed coordinates and. states to a nonlinear version of the mentioned system. Also, we clarify some misunderstandings about the concept of dressed coordinates. Indeed, now we: prefer to call them renormalized coordinates to emphasize the analogy with the renormalized fields in quantum field theory.